A critique of quantitative easing by the Federal Reserve System and the European Central Bank - Pichová, Simona; Černohorský, Jan; Kacerová, Markéta; Žíla, Jan (My University, 2023)
The application of quantitative easing tools by certain central banks has been and continues to be the subject of professional debate. Therefore, this paper aims to assess an alternative scenario to the use of quantitative easing. We have used counterfactual analysis to estimate GDP growth in the US and in the eurozone for the period during which quantitative easing was implemented, i.e., since 2009 in the US and since 2015 in the eurozone. We used a vector autoregression (VAR) model for the analysis. We concluded that, in retrospect, the use of quantitative easing appears to be unwarranted. While there was slightly higher GDP growth in the eurozone than there would have been without quantitative easing, there was no smoothing of the economic cycle. At the same time, returning to the inflation target took a relatively long time. In the US, quantitative easing prevented an initial slide into a deep recession and smoothed the economic cycle over the medium term. Overall, however, quantitative easing has mostly had a negative effect. One major negative is that when this instrument is used over a long time period, economic subjects gradually come to see it as a standard tool. Furthermore, inflation, central banks’ main objective, did not rise rapidly over the period in question; on the contrary, over the long term, quantitative easing has become one of the factors behind today’s higher inflation rates. An excessive monetary supply has created imbalances in the financial markets and has been a factor in price bubbles in the stock, bond, and property markets. Last but not least, it has increased moral hazard for governments, which have gone further into debt without difficulty. At the same time, central bank independence was violated, which has caused an abnormal increase in the central banks’ balance sheets. We therefore recommend that this unconventional monetary policy instrument only be used in the short term for emergency situations as a clear central bank response to stabilize the economy.
Kritika kvantitativního uvolňování prováděná Federálním rezervním systémem a Evropskou centrální bankou
Keywords: Quantitative easing; the Federal Reserve System; the European Central Bank; kvantitativní uvolňování; Federální rezervní systém; Evropská centrální banka